OTU-026 Feasibility & economic evaluation – chromoendoscopy for detecting proximal serrated neoplasia: randomised controlled trial, conscop. (8th June 2018) - Dolwani, Sunil; Ramaraj, Rajeswari; Hurt, Chris; Farr, Angela; Morgan, Meleri; Williams, Namor; Phillips, Ceri; Williams, Geraint; Gardner, Georgina; Porter, Catherine; Sampson, Julian; Hillier, Sharon; et al.
Abstract : Introduction: Most post-colonoscopy interval colorectal cancers occur in the proximal colon. Serrated lesions are often pre-cursors to these and considered harder to detect. Chromocolonoscopy may improve detection rates, however the safety, feasibility and economic impact of this intervention to detect and resect proximal serrated neoplasia are not known. Methods: We conducted a parallel randomised controlled, open label trial within centres in the Bowel Screening Wales (BSW) programme. Participants testing positive on Faecal Occult Blood Test were randomised to standard white light colonoscopy or chromocolonscopy. Randomisation was performed centrally via an internet based minimisation algorithm. Data from index colonoscopies and associated clearance procedures were analysed. All proximal polyps were centrally reviewed by an expert pathology panel. Results: Between November 2014 and June 2016, 741 people (360 white light, 381 chromocolonoscopy) from all BSW centres consented to participate in the study and all were included in the analysis. For participants in the chromocolonoscopy arm, the procedure took an average of 6.3 (95% CIs: 4.2–8.4) min longer but serious adverse reaction rates, bowel preparation scores, completion rates, endoscopist assessment of procedural difficulties, procedure comfort scores, technical quality indicators, and types of sedation were similar in each arm. The proximal serrated polyp detection rate was significantly higher in the chromocolonoscopy arm (23/360 (6.4%) vs 45/381 (11.8%); univariable OR 1.96, 95% CI: 1.16–3.32, p=0.012; multivariable OR 2.04, 95% CI: 1.18–3.50, p=0.010). A 1% likelihood increase in additional significant serrated lesions retrieval would cost £35.22. Conclusions: A large RCT of index chromocolonoscopy powered for improved significant serrated polyp detection within a screening population is safe and feasible and initial efficacy results are encouraging. ClinicalTrials.gov: NCT01972451 .